2021
DOI: 10.3390/jtaer16050089
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Self-Construal and Perceived Risk on Technology Readiness

Abstract: This paper explores how different self-construals interact with perceived risk and influence tourism consumers’ technology readiness toward tourism mobile apps. The study used 284 tourist participants to show that tourism consumers, regardless of self-construal type, have a negative perception of technology readiness when they perceive a high level of risk. Furthermore, those with independent self-construal have a more positive perception of technology readiness than those with an interdependent self-construal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Along with characteristics of restaurant choices (e.g., more flexible task and less complex decision), consumers have relatively high levels of uncertainty in their choices regarding restaurants compared to purchasing products. Therefore, consumers are more likely to be involved in searching for information to reduce the perceived risk of their decisions; they keep open the option to change their decisions according to the context they face, such as information obtained from external sources, rather than adhering to the initial planned decision [34,35]. In addition, current consumers can freely share and upload their restaurant consuming experiences with others, utilising developed mobile tools [36][37][38].…”
Section: Consumers' Restaurant Decision Making and Experiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…Along with characteristics of restaurant choices (e.g., more flexible task and less complex decision), consumers have relatively high levels of uncertainty in their choices regarding restaurants compared to purchasing products. Therefore, consumers are more likely to be involved in searching for information to reduce the perceived risk of their decisions; they keep open the option to change their decisions according to the context they face, such as information obtained from external sources, rather than adhering to the initial planned decision [34,35]. In addition, current consumers can freely share and upload their restaurant consuming experiences with others, utilising developed mobile tools [36][37][38].…”
Section: Consumers' Restaurant Decision Making and Experiencesmentioning
confidence: 99%
“…(Respondent 22, male, aged [35][36][37][38][39][40][41][42][43][44] Many of the interviewees stated that utilising social media on smartphones is convenient because of portability while they were en route and when they needed to decide on a restaurant. In addition, some respondents utilised social media for their restaurant selection process, as they regarded that social media use based on smartphones did not interrupt their media use activities, regardless of time and place.…”
Section: Research Questionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the current findings extend the emerging research stream that advocates for the significance of self-construal in individual behavior by linking self-construal to privacy-related decision-making. [17][18][19] Furthermore, showing the mediating effect of regulatory focus open up a myriad of potential implications of regulatory focus theory to the privacy literature. Third, prior research suggested that people are reluctant to share their private data when they are exposed to information framed as a threat or danger.…”
Section: Introductionmentioning
confidence: 99%